ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI FOOT MASSAGE THERAPY TERHADAP TINGKAT KECEMASAN PASIEN HEMODIALISA DI RUMAH SAKIT BHAYANGKARA TK.I RADEN SAID SUKANTO - Afifah Arum Meylany, (2022)
Patients on long-term hemodialysis will be concerned about the uncertainty of the disease, the timing of hemodialysis, and chronic pain. It can made patients frustration and feeling anxiety. One of anxiety management is relaxation with foot massage therapy. Foot massage therapy is alternative therapy for feels comfort and reduce anxiety, because it provides stimulation to 7,000 nerve cells in the feet. The purpose of this nursing implementing to make sure the effectiveness of foot massage therapy in reducing the anxiety level of hemodialysis patients. The patient's anxiety level was measured using the Hamilton Anxiety Rating Scale (HARS) instrument. The total HARS value of hemodialysis patients who are more than 14 will be given foot massage therapy for 10 minutes before hemodialysis begins. The results found by nurses after providing foot massage therapy intervention were nurses saw a significant different value in the patient's anxiety level before being given an intervention with a total value of HARS 20 and after being given an intervention with a total value of HARS 10. Therefore, it can be concluded that foot massage therapy is effective in reducing anxiety level of hemodialysis patients.